Analisis Pemakaian Afiks pada Kumpulan Puisi Malu (Aku) Jadi Orang Indonesia Karya Taufiq Ismail - Kencanawati, Ni Wayan; Suparwa, I Nyoman; Sri Satyawati, Made (Humanis, 2017)
This Study is analyzed  the affixes with source of data, which is  the collection poetry of Malu (Aku) Jadi Orang Indonesia by Taufiq Ismail . This research is intended to know the use of words and analyze the use of affixes seen from the form, function, and meaning. The method of data collection that used by researcher was observation method with uninvolved conversation observation technique and writing technique. In analyzing data, the researcher used distributional method with change technique and also analytical method, meanwhile in the presentation of data analysis methods used are formal and informal methods. The result showed that the used of affixes consist of singular word and complex word which is affixes word, repetition word, compound word and also the used of klitik word. The singular word had found consist of 22.717 and the compound word was 5.184. So, on the collection poetry Malu (Aku) Jadi Orang Indonesia by Taufiq Ismail was tend use a singular word. Affixes had found on the collection of poetry was prefix meng-, ke-, ber-, di-, se-, per-, peng-, and ter- ; inf fixes -el- , -er-, and -em- ; suf fixes -an, -i, -kan, and -nya; and confict ke-…-an, ber-…-an, per-…-an, peng-…-an, and se-…-nya; and also simulf fixes meng-…-kan, di-…-kan, memper-…-kan, diper-…-kan, memper-…-i, meng-…-i, ter-…-kan, per-…-kan.